Вторичные паразиты непарного шелкопряда (Ocneria dispar L.) в очагах вредителя в Нижнем Приднепровье - Котенко, А.Г. (Вестник зоологии, 1976)
The studies carried out in the Lower Dnieper area resulted in detecting 16 species of secondary parasites of Ocneria dispar L. 13 of them are presented for the first time for the given region.